Library Staff Research Activities of “Top 5-100” Russian Universities. / Actividades de investigación del personal de biblioteca de las universidades rusas “Top5-100” . - FAGIMOVNA PLOTNIKOVA, NAILYA; NIKOLAEVICH STRUKOV, EVGENY; GERMANOVNA KONDRATEVA, IRINA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The main role in university competitiveness realizes a university library as one of the structural unit within Russian universities’ project “Top 5–100” to promote the mission of the university and its academic community, provide the best practices and innovations in education and research process, in managing and studying information and preserving the intellectual and cultural heritage. The authors discuss various ways to improve the research activity of university staff, explore the role of university libraries as centers of information resources, identifying trends in the development of modern university libraries that intend to increase the publication activity of university staff. RESUMEN El papel principal en la competitividad universitaria es la biblioteca universitaria como una de las unidades estructurales dentro del proyecto de las universidades rusas "Top 5–100" para promover la misión de la universidad y su comunidad académica, proporcionar las mejores prácticas e innovaciones en el proceso de educación e investigación, en la gestión y estudio de la información y la conservación del patrimonio intelectual y cultural. Los autores discuten diversas formas de mejorar la actividad investigadora del personal universitario, exploran el papel de las bibliotecas universitarias como centros de recursos de información, identificando tendencias en el desarrollo de las bibliotecas universitarias modernas que pretenden incrementar la actividad editorial del personal universitario.